Contesting the Iron Fist : Advocacy Networks and Police Violence in Democratic. - Fuentes, Claudio (Routledge, 2004)
This work analyses the interactions and international connections of the 'civil rights' and 'pro-order' coalitions of state and societal actors in Argentina and Chile.